The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/07055900.2017.1401973
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Future Trends in Biogeochemical Conditions in the Northwest Atlantic Using CMIP5 Earth System Models

Abstract: We use the results from eight of the Earth System Models (ESMs) made available for the Fifth Assessment Report of the Intergovernmental Panel on Climate Change to analyze the projected changes in biogeochemical conditions over the next 50 years in the northwest Atlantic. We looked at the projected changes using the Representative Concentration Pathway 8.5 scenario in the 100-400 m depth range over a large region and at more specific locations to assess the relevance of using these outputs to force a regional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 100 publications
3
32
0
2
Order By: Relevance
“…To investigate potential future distributions of DO, we currently rely on biogeochemical ocean models that couple physical, chemical, and biological processes. High-resolution regional models are best suited to address changes in the coastal ocean, since global models still lack sufficient resolution to represent continental shelf processes properly, particularly in the Scotian Shelf area (Lavoie et al, 2013). Regional ocean models can simulate past and present conditions, for which they can be validated against observations from ships, moorings, buoys, satellites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate potential future distributions of DO, we currently rely on biogeochemical ocean models that couple physical, chemical, and biological processes. High-resolution regional models are best suited to address changes in the coastal ocean, since global models still lack sufficient resolution to represent continental shelf processes properly, particularly in the Scotian Shelf area (Lavoie et al, 2013). Regional ocean models can simulate past and present conditions, for which they can be validated against observations from ships, moorings, buoys, satellites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Rickard et al (2016) summarized that oceanographic variables in CMIP5 models reveal better agreement across all models compared to biochemical ones. Lavoie et al (2013) detected that GFDL and MPI models better represent nitrate concentrations, and the GFDL model best represents salinity among other considered models in the Labrador Sea. In our study, these models were also selected as the best for the Labrador Sea.…”
Section: Resultsmentioning
confidence: 93%
“…This might be improved by implementing zooplankton projections into the hydrodynamic model through a physical–biogeochemical coupling approach (e.g. Lavoie, Lambert, & Gilbert, ). Zooplankton are considered when hydrodynamic model is coupled to biogeochemical model (physical–biogeochemical coupling) in which nutrient, phytoplankton, zooplankton and detritus are state variables of the biogeochemical model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, this study revealed zooplankton abundances as a key variable in determining mackerel spawning habitat but could not be incorporated in the projections. This might be improved by implementing zooplankton projections into the hydrodynamic model through a physical-biogeochemical coupling approach (e.g Lavoie, Lambert, & Gilbert, 2017)…”
mentioning
confidence: 99%